A study of autologous serum therapy in patients of chronic urticaria at a tertiary care center in western India - Madhudiya, Rinkal; Parmar, Vimesh; Vora, Deval (International Journal of Research in Dermatology, 2024)
Background: Chronic urticaria (CU) is a common and troublesome dermatosis for patients. Approximately 30-50% of patients with CU have an autoimmune basis for their condition, as shown by a positive skin test for ASST, this subgroup is known as Autoreactive chronic urticaria. autologous serum therapy (AST) is considered a potential curative for this auto-reactive subgroup. Our study aimed to find out the efficacy of AST in both ASST positive and ASST negative CU patients. Methods: A cohort of 100 patients of CU were prospectively analyzed for incidence of ASST (+) patients out of total and efficacy of autologous serum injections for sequential 6 weeks in both ASST (+) and ASST (-) CU patients. The response of AST was recorded by the urticaria total severity scale (TSS) every week for 6 weeks and at 18 weeks. Results: The mean baseline TSS in the ASST (+) group was 12.14±1.66 and in the ASST (-) group was 11.77±1.45 (p-value- 0.5). The mean TSS at 18 weeks in the ASST (+) group was 1.30±1.51 and in the ASST (-) group was 2.17±2.02 (p-value-0.151). At 18 weeks of treatment, complete clearance was present in 44.6% of the ASST (+) group and 31.4% in the ASST (-) group (p value-0.151). Conclusions: AST can be considered as a first line of treatment, in patients of CU irrespective of the results of ASST, which is cost-effective and has long-lasting effects.